QTL mapping for different resistant starch subtypes identified a superior haplotype balancing high RS content and relatively good eating and cooking qualities in rice - Liang, Cheng; Bu, Yuesi; Xu, Haoyang; Ma, Xuemei; Zhang, Xueying; Hu, Tian; Xiang, Xunchao; Hu, Yungao; Xu, Liang (Frontiers in Plant Science, 2026)
Resistant starch (RS) plays an important physiological role in maintaining human health. However, increasing RS content in rice often comes at the cost of deteriorating its eating and cooking qualities (ECQs). In order to address this conflict, we conducted co-localization quantitative trait locus (QTL) analysis for RS in raw rice flour (RSm), cooked rice (RSc), retrograded rice (RSr) along with correlation analysis between RS and ECQs, using recombinant inbred line (RIL) populations derived from a cross of CG133R and Javanica 22. A total of 33 QTLs associated with RSm, RSc, RSr, RSa, and RSb were identified. These included two major QTLs on choromosome 6 (Wx and SSIIa), and several novel minor-effect QTLs such as q2ERSc3.2, q2ERSb5.1, and q2ERSb9.1 on choromosome 3, 5 and 9, respectively. Wx accounted for 27.34%, 64.16%, 68.07%, 29.95%, and 39.62% of the phenotypic variance for RSm, RSc, RSr, RSa (RSm-RSc), and RSb (RSr-RSc), respectively. Meanwhile, SSIIa explained 42.42%, 17.82%, 14.09%, and 51.16% of the phenotypic variance for RSm, RSc, RSr, and RSa. Furthermore, the thermal and retrogradation properties demonstrated positive correlations with RSm, but negative correlations with RSc and RSr, which was attributed to the differential regulation of Wx and SSIIa. Wxa-SSIIaG-GC regulated high RSm and RSa, while Wxa-SSIIaG-TT significantly increased RSc and RSr. Notably, Wxa-SSIIaG-TT haplotype improved the rice ECQs by reducing gelatinization temperature, preventing retrogradation and enhancing viscosity properties. Thus, this study identified an excellent haplotype, Wxa-SSIIaG-TT, which enhanced RSc and RSr and improved rice ECQs, providing useful information for breeding high-RSc rice with a relative superior quality.